Achyranthoside D (AD) improve intervertebral disc degeneration through affect the autophagy and the activation of PI3K/Akt/mTOR pathway. (29th October 2022) - Zhang, Chao; Li, Zhaoyong; Li, Linghui; Li, Shuofu; Yang, Lei; Chen, Long; Zhang, Xiao; Yang, Shaofeng; Guo, Yantao
Purpose: This study aims to explore the potential mechanism of Achyranthoside D (AD) in improving intervertebral disc (IVD) degeneration (IDD). Methods: The IDD model of SD rats and nucleus pulposus cells (NPCs) was established by lumbar cone annulus puncture and tert-butyl peroxide, respectively. Cell proliferation was detected by CCK8 assay. Apoptosis was detected by flow cytometry and TUNEL staining. IVD tissue injury was observed by HE staining. Alcian blue staining observed the glycoprotein secretion in IVD. Monodansylcadaverin (MDC) staining was used to detect the formation of autophagosomes. The LC3 expression was tested by immunofluorescence. The type II collagen, aggrecan and MMP3 expression were detected by ELISA. RT-qPCR was used to detect the Casp 3, Bax, Bcl2, Acan, Col2a1 and Mmp3 expression. The LC3, P62, type II collagen, aggrecan, Beclin1, Akt, MMP3, p-mTOR, PI3K, mTOR, p-PI3K and p-Akt expression were analyzed by western blot. Results: The IVD tissue damage and apoptosis occurred in the Model group, and the glycoprotein secretion decreased. Compared with Model group, AD-H group alleviated the injury of IVD tissue, inhibited the apoptosis of cells, and increased the secretion of glycoprotein. 40 μg/mL AD restored the proliferation activity of NPCs. Compared to the Normal group, the NPCs apoptosis increased, the Collagen II, aggrecan and Bcl2 expressions were significantly decreased, the MMP3, Bax and Casp 3 expression were significantly increased, and the LC-3 II/I expression in IVD tissues were increased significantly in Model group, all of which was reversed in AD group. AD promoted the p-Akt, p-PI3K, p-mTOR, LC-3 II/I and Beclin1 expression, inhibited the P62 expression to alleviate the damage of nucleus pulporeus cells and the degeneration of IVD. Conclusion: AD improved IDD by affecting the PI3K/Akt/mTOR pathway and autophagy.